RUMAH KOMPOS SEBAGAI MEDIA KOMUNIKASI LINGKUNGAN: MENINGKATKAN PARTISIPASI WARGA DESA CIAMPEA ASRI DALAM PENGELOLAAN SAMPAH - Ihsan Suri; Dhiya Rizky Meylinda; Muhammad Hadjid Syakir; Alviena Rachma Assyifa; Indira Maisa Zahira (LPPM Universitas Abdurrab, 2026)
The issue of organic waste management in rural areas remains an environmental challenge that requires community-based participatory approaches. Ciampea Asri Village, located in Ciampea District, Bogor Regency, is a densely populated area experiencing a significant increase in household waste over the past few years. Most organic waste, such as food residues and leaves, is either burned or disposed of in temporary dumps, contributing to air pollution and environmental degradation. Through a community service program grounded in environmental communication, this activity aims to enhance community participation in organic waste management by developing and utilizing a Compost House as an educational and environmental communication medium. The implementation method uses a Participatory Action Research (PAR) approach which involves 35 residents of RW 06 Ciampea Asri Village in the problem identification stage, composting training, and compost house construction, to digital-based environmental campaigns. Evaluation was conducted through pre-tests and post-tests to assess increased knowledge, as well as field observations to see changes in waste management behavior in ecological aspects in the community. The results indicated a 31% increase in environmental literacy, the processing of 180 kg of organic waste into 50 kg of usable compost in a weekly. This program contributes to achieving SDG 11 (Sustainable Cities and Communities), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action) by fostering ecological awareness, self-reliance, and a culture of collaboration among the residents of Ciampea Asri Village.